2022
DOI: 10.1021/acsapm.2c01630
|View full text |Cite
|
Sign up to set email alerts
|

Immiscible Polymer Blends Compatibilized through Noncovalent Forces: Construction of a “Quasi-Block/Graft Copolymer” by Interfacial Stereocomplex Crystallites

Abstract: Interfacial compatibilization is acknowledged to be the most effective approach to improve interfacial strength between the thermodynamically immiscible components of polymer blends. However, the compatibilizer, mainly achieved by graft or block copolymers, necessarily connected by covalent bonds, can rarely be satisfied presently. Herein, we propose a concept of “quasi-block/graft copolymer” to compatibilize the immiscible polyolefin elastomer (POE) and poly(styrene-acrylonitrile-glycidyl methacrylate) (SAG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…The SC interfacial layer was achieved by the PLLA and PDLA that were reactively grafted on the polyolefin elastomer (POE) and poly(styreneacrylonitrile-glycidyl methacrylate) (SAG), respectively, imparting high modulus and rigidity, resulting in improved toughness for POE/SAG blends. 22 As expected, a compatibilizer that decreases interfacial tension accompanied by the rigid interface constructed by SC crystallite enhanced the interfacial strength, which could make a co-continuous morphology in the PLLA/PBAT blend.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…The SC interfacial layer was achieved by the PLLA and PDLA that were reactively grafted on the polyolefin elastomer (POE) and poly(styreneacrylonitrile-glycidyl methacrylate) (SAG), respectively, imparting high modulus and rigidity, resulting in improved toughness for POE/SAG blends. 22 As expected, a compatibilizer that decreases interfacial tension accompanied by the rigid interface constructed by SC crystallite enhanced the interfacial strength, which could make a co-continuous morphology in the PLLA/PBAT blend.…”
Section: Introductionsupporting
confidence: 63%
“…Recently, Li et al reported the PLLA/PBAT blends with significant impact strength, in situ compatibilized by poly­(styrene- co -glycidyl methacrylate)- graft -( d -lactide) (SG- g -PDLA), which formed a rigid interface through the formation of stereocomplex crystallites, inducing a stable co-continuous morphology. The SC interfacial layer was achieved by the PLLA and PDLA that were reactively grafted on the polyolefin elastomer (POE) and poly­(styrene-acrylonitrile-glycidyl methacrylate) (SAG), respectively, imparting high modulus and rigidity, resulting in improved toughness for POE/SAG blends . As expected, a compatibilizer that decreases interfacial tension accompanied by the rigid interface constructed by SC crystallite enhanced the interfacial strength, which could make a co-continuous morphology in the PLLA/PBAT blend.…”
Section: Introductionmentioning
confidence: 70%
“…The compatibility of TPU/MVQ blends is very poor, and the addition of some compatibilizers is an effective way to solve this problem, which can also increase the interfacial adhesion and optimize the morphology of TPU/MVQ blends. [9][10][11][12][13][14][15] In early studies, the compatibilizers of TPU/MVQ blends mainly included some block copolymers, 16,17 graft copolymers [18][19][20][21] and homo-copolymers, 10 such as the polydimethylsiloxane-polybutadiene-polyurethane triblock copolymer (PU-PB-PDMS), 22 the homo-copolymer of ethylene and methyl acrylate (EMA), 10 and the polyurethane-polysiloxane copolymers (PU-co-PSi). 9 However, the molecular chains of these copolymer compatibilizers are prone to curling and folding, and then form micelles and migrate into one phase during the blending process.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Electrical properties of polymer blends were engineered by combining polymers with different electrical conductivities, dielectric constants, and charge carrier mobilities. [2,3] This allows for the creation of materials with desired electrical insulation, conductivity, or dielectric properties, suitable for a wide range of applications including electronics, sensors, and energy storage systems. [4] Polyvinyl chloride (PVC) is a versatile polymer that exhibits a range of electrical and thermal properties, making it suitable for various electrical and thermal applications.…”
Section: Introductionmentioning
confidence: 99%